Association Between Anxiety and New Organ Failure, Independently of Critical Illness Severity and Respiratory Status: A Prospective Multicentric Cohort Study. Issue 10 (October 2020) - Mazeraud, Aurélien; Polito, Andrea; Sivanandamoorthy, Sivanthiny; Porcher, Raphaël; Heming, Nicholas; Stoclin, Annabelle; Hissem, Tarik; Antona, Marion; Blot, François; Gaillard, Raphaël; Chrétien, Fabrice; Annane, Djillali; et al.
Abstract : Objectives: Anxiety results from the anticipation of a threat and might be associated with poor outcome in the critically ill. This study aims at showing that anxiety at admission in critically ill patients is associated with new organ failure over the first 7 days of ICU hospitalization independently of baseline organ failure at admission. Design: Prospective multicenter cohort study. Setting: Three mixed ICU from April 2014 to December 2017. Patients: Coma-, delirium-, and invasive mechanical ventilation-free patients admitted to the ICU were included. Interventions: None. Measurements and Main Results: "State anxiety" was assessed using the state component of the State-Trait Anxiety Inventory State. Severity of illness was measured using Simplified Acute Physiology Score II and Sequential Organ Failure Assessment scores. Primary endpoint was a composite of occurrence of death or new organ failure in the first 7 days after admission. Three hundred ninety-one patients were included; 159 of 391 women (40.7%); median age 63 years (49–74 yr); median Simplified Acute Physiology Score II 28 (19–37). Two hundred three out of 391 patients (51.9%) reported moderate to severe anxiety (State-Trait Anxiety Inventory State ≥ 40). One hundred two out of 391 patients (26.1%) developed a new organ failure. After adjustment to Simplified Acute Physiology Score II and Sequential Organ Failure Assessment, State-Trait Anxiety Inventory State greater than or equal to 40 was associated with the primary endpoint (odds ratio, 1.94; 95% CI, 1.18–3.18; p = 0.009) and respiratory failure. In post hoc analysis, State-Trait Anxiety Inventory State greater than or equal to 40 was associated with new organ failure independently and notably of respiratory status at admission (dyspnea-Visual Analogic Scale and PaCO2 ≥ 45 mm Hg). Conclusions: Moderate to severe anxiety at ICU admission is associated with early occurrence of new organ failure in critically ill patients, independently of respiratory status and severity of critical illness. The causality link could be addressed in an interventional trial. Abstract : Supplemental Digital Content is available in the text.